Effect of defects on wear behavior in ta-C coating prepared by filtered cathodic vacuum arc deposition - Lee, Woo-Young; Jang, Young-Jun; Tokoroyama, Takayuki; Murashima, Motoyuki; Umehara, Noritsugu (Diamond and related materials, 2020)
This study examined the tribological behavior of a ta-C coating fabricated at a substrate bias of −100 V via filtered cathodic vacuum arc (FCVA) deposition. Defects in the ta-C coating were categorized as droplets, pores, and spikes, considering the morphological, structural, and mechanical properties of the ta-C surface. A friction test was conducted at 170 °C in ambient air using a ball-on-disk tribometer. The friction coefficient was 0.08 during the steady state and the wear rate was 4.3 × 10−6 mm3/Nm. To explain the friction and wear behavior, the morphological and structural properties of the defects in the designated area were compared among different sliding cycles. [Display omitted] •Defects in the ta-C coating fabricated by FCVA were classified as droplets, pores, and spikes•Clarified effect of each defects on tribological behavior at high temperature at 170 °C•Spike and droplet have a shape of convex whereas pore is in the form of concave.•Spikes having similar properties of matrix of ta-C remain on the ta-C surface even after high-temperature friction test.•Spikes and droplet prevent tribolayer formation on Si3N4 ball in running-in region and steady state, respectively.